CORRELATION BETWEEN BLOOD PRESSURE AND URINE CA/CR RATIO WITH PREECLAMPSIA IN NULLIPARA WOMEN - R Dehghani Firouzabadi (Babol University of Medical Sciences, 2007)
BACKGROUND AND OBJECTIVE: Preeclampsia is a multisystemic disorder of pregnancy. Cause of this disorder is still unknown. Its Incidence is 5-7% of all pregnancies. The aim of the present study was to evaluate the diagnostic value of blood pressure and urine Ca/Cr ratio in second trimester for prediction of preeclampsia.METHODS: This cross sectional study was performed on 120 nullipara women referred to Shahid Sadoghi hospital during one year. Questionnaire was included risk factors such as blood pressure of second and third trimester, urine Ca/Cr ratio in second trimester and urine albumin in third trimester.FINDINGS: One hundred-twenty nullipara women with the mean age of 21±2.4 years were evaluated. From 84 women with normal blood pressure in the 2nd trimester, 82 (97.6%) had no preeclampsia and 2 (2.4%) of them showed preeclampsia. From 36 women with high blood pressure in the 2nd trimester, 30 (83.3%) had no preeclampsia and 6 (16.7%) of them showed preeclampsia. There was a significant difference between blood pressure of second trimester and preeclampsia (p=0.009), while there was not significant difference between urine Ca/Cr ratio in the second trimester and preeclampsia. CONCLUSION: Blood pressure of the second trimester is a useful predictor for preeclampsia, while urinary Ca/Cr ratio can not predict preeclampsia.